Islet-cell Carcinoma (Zollinger—Ellison Syndrome) with Fulminating Adrenocortical Hyperfunction and Hypokalemia - Geokas, M. C. (1965)
The production of ACTH-like material by tumours arising in non-endocrine tissue may initiate severe adrenocortical hyperfunction. The pathogenesis and clinical and laboratory features of Cushing's syndrome associated with such tumours are characteristic. The autonomous production by the tumour of ACTH-like material cannot be suppressed by exogenous corticoids. The onset of clinical symptoms is rapid; muscle wasting, general weakness, thirst and peripheral edema predominate, and the classical signs of Cushing's syndrome may be absent. High levels of plasma 17-hydroxycorticosteroids and urinary 17-hydroxycorticosteroids and 17-ketosteroids, usually with normal levels of urinary aldosterone, commonly occur. Hypokalemic alkalosis unresponsive to replacement therapy may cause death. In the case reported herein, the intriguing possibility exists that two hormone-like substances were produced by the primary growth and its metastases: one, ACTH-like, to account for the adrenal hyperplasia and Cushing's syndrome; and another, gastrin-like, giving rise to the ulcerogenic diathesis.